'I wish I were a plumber!': Transnational class reconstructions across migrant experiences among Hong Kong's professionals and managers. (November 2020) - Lui, Lake; Curran, Sara R
This study examines processes of class construction within a transnational community of professionals and managers who are emigrants, returnees, and non-migrants. Building on Bourdieu's class analysis and literature on transnational migration, the article examines how class statuses are supported by moral claims based on varying transnational mobility strategies. The authors draw their results from qualitative interviews with 45 Hong Kong respondents in Hong Kong and Canada. They find that despite Hong Kong emigrants' loss of economic capital due to de-professionalization, their cultural and symbolic claims frame an alternative set of norms about their life successes. Returnees claim to have the best of both worlds having amassed economic capital, while making social distinctions from stayers in terms of their globalized cosmopolitan imaginaries. Stayers appear envious of emigrants' and returnees' flexibility and seek to accumulate economic capital for future retirement migration or to send their children abroad. Respondents' moralizing discourses reveal a social field defining within-class distinctions apart from hyper-concerns of upward mobility through material gains. Nuanced class distinctions articulate values around freedom of space, time, and expression not readily accessible to residents remaining in Hong Kong.